2020
DOI: 10.1186/s40478-020-00917-6
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of EGFR amplification and EGFRvIII variant using digital PCR-based method in glioblastoma

Abstract: Epidermal growth factor receptor (EGFR) amplification and EGFR variant III (EGFRvIII, deletion of exons 2-7) are of clinical interest for glioblastoma. The aim was to develop a digital PCR (dPCR)-based method using locked nucleic acid (LNA)-based hydrolysis probes, allowing the simultaneous detection of the EGFR amplification and EGFRvIII variant. Sixty-two patients were included. An exploratory cohort (n = 19) was used to develop the dPCR assay using three selected amplicons within the EGFR gene, targeting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Next, we considered focal (<3 Mb) ( Krijgsman et al., 2014 ) amplifications (defined as copy number ≥ 5) ( Fontanilles et al., 2020 ) and homozygous deletions (copy number = 0) in oncogenes and tumor suppressor genes respectively, to understand if these events are associated with CPI response. The most significant association was found to be significantly lower rates of CPI response in tumors with CCND1 amplification (response rate = 16.3%) compared to wild-type (26.6%) (p = 4.8 × 10 −2 ; Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we considered focal (<3 Mb) ( Krijgsman et al., 2014 ) amplifications (defined as copy number ≥ 5) ( Fontanilles et al., 2020 ) and homozygous deletions (copy number = 0) in oncogenes and tumor suppressor genes respectively, to understand if these events are associated with CPI response. The most significant association was found to be significantly lower rates of CPI response in tumors with CCND1 amplification (response rate = 16.3%) compared to wild-type (26.6%) (p = 4.8 × 10 −2 ; Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…B-ASOs have a dual therapeutic potential against cancer cells: anti-EGFR inhibitory and boron carrier ( 10 B) delivery for BNCT which we have described previously [ 23 , 24 , 26 , 27 , 44 ]. Importantly, the ASO sequences of these structures were designed to be effective silencers towards EGFR mRNA, as well as EGFR variant III mRNA [ 14 , 61 ]. We observed that B-ASO (80 pmol) can be freely taken up into A431 cells and mediated by FESAN-EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…EGFRvIII undergoes a 6–273 amino acid deletion at exon 2–7, encoding the extracellular domain of EGFR 133 , and EGFRvIII can undergo dimerization via a ligand-independent activation pathway 132 . EGFRvIII differs from mutant EGFR on the extracellular domain, namely due to the deletion of certain amino acids causing slow receptor internalization, as well as a slower constitutively phosphorylation level compared to EGFR isoform 1 134 . The results of NGS showed the downregulation of EGFRvIII due to CCA-1.1 treatment.…”
Section: Discussionmentioning
confidence: 99%